1996
DOI: 10.1177/002246699603000201
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Inclusion Only, Pull-Out Only, and Combined Service Models for Students with Mild Disabilities

Abstract: The debate on how to best deliver educational services to students with disabilities continues without substantial research on model efficacy. This study compared the inclusion only, pull-out only, and combined services models for a sample of elementary students with mild disabilities. Results indicate that teacher satisfaction and student progress in reading were significantly greater for the combined services model. These data support renewed commitment to the continuum of services. Reasons for the success o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 10 publications
1
52
3
Order By: Relevance
“…According to Freeman and Alkin, the benefits of inclusion were more pronounced when students were fully included rather than partially included. This differs from the conclusions drawn by Marston's (1996) study of students with learning disabilities that reported that a combined service model was more effective than either full inclusion or full segregation. Part of the difference could be accounted for by the nature of the disabilities included in the studies.…”
Section: Inclusion and Student Outcomescontrasting
confidence: 99%
See 2 more Smart Citations
“…According to Freeman and Alkin, the benefits of inclusion were more pronounced when students were fully included rather than partially included. This differs from the conclusions drawn by Marston's (1996) study of students with learning disabilities that reported that a combined service model was more effective than either full inclusion or full segregation. Part of the difference could be accounted for by the nature of the disabilities included in the studies.…”
Section: Inclusion and Student Outcomescontrasting
confidence: 99%
“…Reviewing the literature has resulted in the identification of several studies that found improvement in academics (Cawley et al, 2002;Freeman & Alkin, 2000;Rea et al, 2002) and others that found inclusion to have little effect on achievement (Marston, 1996;Slavin et al, 1984). However, it is important to note that conclusions based upon academic achievement are limited by the scope of each study, the disability area and age group which each focuses on, and the ways in which data were collected.…”
Section: Inclusion and Student Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Marston (1994), however, pointed to teachers' negative attitudes. There is a paucity of research involving attitudes in special education teachers.…”
Section: Teachers' Attitudes Towards Pupils With Special Needsmentioning
confidence: 99%
“…The resource room is especially important when it supports the general curriculum and teachers collaborate to best meet the needs of their students. Marston (1996) found many special education teachers desire the continued use of the resource room.…”
Section: Types Of Service and Placement Optionsmentioning
confidence: 99%